2019
DOI: 10.35940/ijitee.b7662.129219
|View full text |Cite
|
Sign up to set email alerts
|

Research of Formal-Kinetic Regularities of the Curing Process of Low-Viscosity Epoxy Binder

Islam Alexandrovich Alexandrov,
Alexey Vyacheslavovich Kapitanov,
Alexander Nikolaevich Muranov*
et al.

Abstract: The expanding range of components intended for manufacturing products of polymer composite materials is often not accompanied by comprehensive information on the characteristics and recommended technological curing modes. The relevance and practical significance of this investigation are based on the need to predict rational technological modes for curing products of polymer composite materials based on the low-viscosity epoxy binder Etal-Inject-SLM, which is in demand in the manufacture of products from polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Based on the results obtained, it can be concluded that the errors of the target parameters arise from the simulation complexity of the manufacture of products from composite materials by injection molding methods, requiring the consideration of many factors. The most signifi cant ones are bulk polymerization of the binder and change of its viscosity in the process of compounding and impregnation, the fabric pliability and permeability of the fi brous preform, as demonstrated in papers [12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results obtained, it can be concluded that the errors of the target parameters arise from the simulation complexity of the manufacture of products from composite materials by injection molding methods, requiring the consideration of many factors. The most signifi cant ones are bulk polymerization of the binder and change of its viscosity in the process of compounding and impregnation, the fabric pliability and permeability of the fi brous preform, as demonstrated in papers [12][13][14].…”
Section: Methodsmentioning
confidence: 99%